2011
DOI: 10.1016/j.pec.2011.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Rural–urban differences in discussions of cancer treatment clinical trials

Abstract: Objective Compare the characteristics of rural and urban callers to NCI’s Cancer Information Service (CIS), and explore the association of geographic location and discussion of cancer clinical trials. Methods Using CIS call data from 2006–2008, we assigned a rural or urban designation to caller ZIP codes using Rural-Urban Commuting Area Codes. Calls which discussed clinical trials were analyzed using univariate and multivariate analyses. Results The CIS received 227,579 calls from 2006–2008 where geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…To achieve diversity in biomedical research participation, health systems including safety‐net systems serving diverse populations need to have the capacity and willingness to engage with research at the institutional level. As noted in prior studies, lack of access to research‐intensive academic medical centers limits access to cutting‐edge research that potentially could reduce health disparities …”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…To achieve diversity in biomedical research participation, health systems including safety‐net systems serving diverse populations need to have the capacity and willingness to engage with research at the institutional level. As noted in prior studies, lack of access to research‐intensive academic medical centers limits access to cutting‐edge research that potentially could reduce health disparities …”
Section: Discussionmentioning
confidence: 93%
“…As noted in prior studies, lack of access to research-intensive academic medical centers limits access to cutting-edge research that potentially could reduce health disparities. 8,9,11,17,27…”
Section: Access To Carementioning
confidence: 99%
See 1 more Smart Citation
“…For example, patients living in rural areas had more unhealthy behaviors and were less likely to participate in colorectal cancer screening; differences in stage at diagnosis, the prevalence of comorbidities, and the treatment received, as well as access to oncology services and options for treatment, could also have contributed to lower survival from colorectal cancer in rural areas . A United States study showed that rural patients are less likely to receive information regarding participation in cancer treatment trials than urban residents, which may contribute to worse survival in rural and remote regions …”
Section: Discussionmentioning
confidence: 99%
“…4,10,1316 Racial and ethnic minorities — particularly African Americans — bear the greatest cancer burden in the United States, so they should be adequately represented in cancer research. 17–19 Under-representation of racial and ethnic minorities also limits the generalizability of research findings.…”
Section: Introductionmentioning
confidence: 99%